The Metabolomics of Chronic Pain Conditions: A Systematic Review. Issue 4 (October 2020) - Aroke, Edwin N.; Powell-Roach, Keesha L.
Background: Chronic pain is a significant public health problem in the United States, affecting approximately 100 million people. Yet there is a lack of robust biomarkers for clinical use in chronic pain conditions. Downstream effects of environmental, genomic, and proteomic variations in individuals with chronic pain conditions can be identified and quantified using a metabolomic approach. Aim/Design: The purpose of this systematic review was to examine the literature for reports of potential metabolomic signatures associated with chronic pain conditions. Methods: We searched relevant electronic databases for published studies that used various metabolomic approaches to investigate chronic pain conditions among subjects of all ages. Results: Our search identified a total of 586 articles, 18 of which are included in this review. The reviewed studies used metabolomics to investigate fibromyalgia ( n = 5), osteoarthritis ( n = 4), migraine ( n = 3), musculoskeletal pain ( n = 2), and other chronic pain conditions ( n = 1/condition). Results show that several known and newly identified metabolites differ in individuals with chronic pain conditions compared to those without these conditions. These include amino acids (e.g., glutamine, serine, and phenylalanine) and intermediate products (e.g., succinate, citrate, acetylcarnitine, and N-acetylornithine) of pathways that metabolize various macromolecules. Conclusion: Though more high-quality research is needed, this review provides insights into potential biomarkers for future metabolomics studies in people with chronic pain conditions.